Effect of leading-edge tubercles and surface corrugations on the performance and cavitation characteristics of twisted hydrofoils - Usta, Onur; Oksuz, Sinem; Celik, Fahri (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study examines the effects of leading edge tubercles (LETs) and surface corrugations (SCs) on the hydrodynamic performance and cavitation development of twisted hydrofoils under non-cavitating and cavitating flow conditions. Detached Eddy Simulation (DES) method is used for cavitating flow simulations, while the unsteady RANS method is utilized for non-cavitating flows. Initially, a benchmark twisted NACA 0009 hydrofoil was simulated under cavitating conditions consistent with the literature to validate the numerical results. Following this validation, a twisted NACA 0015 hydrofoil (Baseline) and its four Corrugated and one Tubercled configurations were analyzed at high Reynolds numbers. To verify the CFD model, a Grid Convergence Index (GCI) based uncertainty assessment was conducted using time-averaged lift coefficients for the twisted NACA 0015 hydrofoil at 3 degrees AoA under cavitating flow conditions. Numerical simulations were then performed at angles of attack (AoAs) of 1 degrees, 3 degrees, 5 degrees, and 7 degrees to evaluate lift, drag, hydrodynamic efficiency, surface cavitation area, and cavitation period, thereby providing a comprehensive understanding of the influence of LETs and SCs. The results indicate that under non-cavitating conditions, the Corrugated hydrofoil achieves higher efficiency than the other configurations at all AoAs. Under cavitating conditions, the Baseline shows the highest efficiency at low AoAs, although the Corrugated and Tubercled designs progressively approach its performance at higher AoAs. The Tubercled hydrofoil effectively delays stall and has less cavitation area for all AoAs than that of Baseline, while the Corrugated geometry achieves the smallest cavitation area at 7 degrees AoA.
Keywords: Cavitation; Twisted NACA 0015 hydrofoil; Leading-edge tubercle; Surface corrugation; Angle of attack; NUMERICAL-ANALYSIS; FLOW; Engineering; Oceanography